2016
DOI: 10.1016/j.ejc.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A sufficient local degree condition for Hamiltonicity in locally finite claw-free graphs

Abstract: Among the well-known sufficient degree conditions for the Hamiltonicity of a finite graph, the condition of Asratian and Khachatrian is the weakest and thus gives the strongest result. Diestel conjectured that it should extend to locally finite infinite graphs G, in that the same condition implies that the Freudenthal compactification of G contains a circle through all its vertices and ends. We prove Diestel's conjecture for claw-free graphs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…So we shall show that the following two theorems can be extended to locally finite graphs and affirmatively answer questions of Stein [ We also give some corollaries of the two theorems whose infinite but locally finite counterparts are corollaries to the infinite versions of those theorems. Similar questions on Hamilton circles in infinite graphs were investigated by Heuer [17,18].…”
Section: Introductionmentioning
confidence: 75%
“…So we shall show that the following two theorems can be extended to locally finite graphs and affirmatively answer questions of Stein [ We also give some corollaries of the two theorems whose infinite but locally finite counterparts are corollaries to the infinite versions of those theorems. Similar questions on Hamilton circles in infinite graphs were investigated by Heuer [17,18].…”
Section: Introductionmentioning
confidence: 75%
“…Several theorems on Hamiltonicity of finite graphs have been extended to Hamilton circles in locally finite graph; for instance, Georgakopoulos [22] extended Fleischner's theorem [21] on the Hamiltonicity of the square of a 2-connected graph, and Heuer [28] and Hamann et al [26] showed that locally finite, claw-free, locally connected graphs have Hamilton circles, extending a result by Oberly and Sumner [35]. Diestel [18] conjectured that Theorem 3.9 could be extended to locally finite graphs, and Heuer [29] proved the conjecture under the additional assumption that the graph is claw-free.…”
Section: Chapter 4 Infinite Graphsmentioning
confidence: 88%
“…The first one, called a Hamilton circle of G, was introduced by Diestel and and Kühn [19], and the other one, called a Hamiltonian curve of G, was introduced by Kündgen, Li and Thomassen [31] (see the definitions of these two concepts in section 2). Some results on the existence of Hamilton circles in infinite locally finite graphs were obtained in [11,22,[25][26][27] The next result on Hamiltonian curves was proved in [31].…”
Section: Figurementioning
confidence: 96%